THE IMPACT OF EXPERIENCE AND EDUCATION ON EMERGENCY MEDICAL RESPONSE OUTCOMES: A CROSS SECTIONAL STUDY ON BOTH NURSES TECHNICIANS AND EMERGENCY MEDICAL SERVICES PROVIDERS - Abdulrahman Mohammad F Almotairi, Abdulrahman Ruhayl Alanazi, Ahmed Abdullah Ruhail Alanazi, Hadi Matar M Aldhafeeri, Saad Jurbua S Alanazi, Talal Saadi Hawas Alshammari (Chelonian Research Foundation, 2022)
This study aims to investigate the influence of experience and education on emergency medical response outcomes among Nurses and Emergency Medical Services (EMS) providers in Saudi Arabia. A cross-sectional survey was conducted among a sample of 500 nurses and EMS providers from various regions of the country. The participants completed a questionnaire assessing their experience, education level, and self-reported performance on key emergency medical response outcomes, such as response time, on-scene time, and patient outcomes. Multiple linear regression analysis was used to examine the predictive power of experience and education on emergency medical response outcomes, while controlling for demographic and work-related variables. The results showed that both experience and education were significant predictors of emergency medical response outcomes, with experience having a stronger impact than education. The findings suggest that EMS providers with more years of experience and higher levels of education tend to have better emergency medical response outcomes. The study highlights the importance of investing in the experience and education of EMS providers to improve the quality and efficiency of emergency medical services in Saudi Arabia. Keywords: emergency medical services, experience, education, response outcomes, Saudi Arabia